2006
DOI: 10.1111/j.1537-2995.2006.00899.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular basis of two novel high‐prevalence antigens in the Kell blood group system, KALT and KTIM

Abstract: The identified KEL mutations of the two probands are novel and inherited. The antigen absent from the red blood cells (RBCs) of Probands 1 and 2 are named KALT and KTIM, respectively. KALT is unique in that it is the only Kell antigen sensitive to treatment of RBCs by trypsin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 20 publications
0
21
0
Order By: Relevance
“…[38] showed an equal level of activity for KEL1 and KEL2, and the authors noted that this was consistent with the predicted location of residue 193. In addition to these enzymatic studies, novel antigens have been mapped onto the Kell model as they have been discovered [39].…”
Section: Modelling Studies Of Blood Group Active Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…[38] showed an equal level of activity for KEL1 and KEL2, and the authors noted that this was consistent with the predicted location of residue 193. In addition to these enzymatic studies, novel antigens have been mapped onto the Kell model as they have been discovered [39].…”
Section: Modelling Studies Of Blood Group Active Proteinsmentioning
confidence: 99%
“…However, the results of Sha et al [38] showed an equal level of activity for KEL1 and KEL2, and the authors noted that this was consistent with the predicted location of residue 193. In addition to these enzymatic studies, novel antigens have been mapped onto the Kell model as they have been discovered [39]. The crystal structure of endothelin-converting enzyme 1 (ECE-1) ectodomain has been solved recently [40].…”
Section: Kellmentioning
confidence: 99%
“…EcoRI-/+ † KEL28-(VONG-)/KEL28+(VONG +) 53 8 862C>T R248W KEL29+ (KALT+)/KEL29-(KALT-) 10 17 1988G>A R623K TfiI+/- † KEL30+ (KTIM+)/KEL30-(KTIM-) 10 baby is at risk during pregnancies in mothers with anti-K. However, because the procedure, although commonly used, is invasive, it should be withheld until the father is typed to determine the potential for a baby with K antigen.…”
Section: R130w R130qmentioning
confidence: 99%
“…Consisting of more than 30 antigens, the Kell blood group system is one of the most polymorphic of the protein blood group systems . Antibodies to antigens in the Kell blood group system are often clinically significant and have caused transfusion reactions and hemolytic disease and anemia of the fetus and newborn .…”
mentioning
confidence: 99%